GENOTYPIC DIFFERENCE IN CADMIUM EFFECT ON AGRONOMIC TRAITS AND GRAIN ZINC AND IRON CONCENTRATION IN WINTER WHEAT - Rebekić, Andrijana; Lončarić, Zdenko (Emirates Journal of Food and Agriculture, 2016)
A pot experiment was conducted to study the effect of soil cadmium contamination on agronomic traits and grain zinc and iron concentration in a set of 51 winter wheat varieties of different origin and year of release. An experiment was set up according to completely randomized design with two treatments (0 and 20 mg Cd kg-1 soil) and four replicates. Results showed that soil cadmium contamination increased grain cadmium concentration for 70 fold in average. All agronomic traits were reduced on cadmium contaminated in comparision to values obtained on an uncontaminated soil. The greatest reduction was observed in grain weight per spike and spike weight (27%) followed by plant weight (25%) and a number of grains per spike (23%). Furthermore, on uncontaminated soil, cadmium concentration in grain was in negative correlation to all agronomic traits (except for 1000 kernel weight) and cultivars year of release. Grain zinc concentration was not affected by soil Cd contamination while grain iron concentration was higher on a Cd contaminated soil in comparison to values obtained on uncontaminated soil.